Optimal Configurations of Mueller Polarimeter for Gaussian–Poisson Mixed Noise - Zheng Hu; Qianhao Zhao; Hui Ma (Applied Sciences, 2022)
The accuracy of the Mueller polarimeter is usually affected by Gaussian–Poisson mixed noise, and by optimizing the instrument matrices of polarization state generator and polarization state analyzer in the measurement system, the estimation variance caused by Gaussian noise can be suppressed, and the estimation variance caused by Poisson noise can be made independent of the sample. However, the optimization procedure usually targets only the numerical value of the instrument matrix without considering how to configure the measurement system to achieve the optimal instrument matrix. In this paper, we investigate how to make the measurement system optimal for different measurement systems by combining geometric optimization on the Poincaré sphere and finally propose a series of measurement configurations for different applications.